2016
DOI: 10.1016/j.cbi.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylesterases: General detoxifying enzymes

Abstract: Carboxylesterases (CE) are members of the esterase family of enzymes, and as their name suggests, they are responsible for the hydrolysis of carboxylesters into the corresponding alcohol and carboxylic acid. To date, no endogenous CE substrates have been identified and as such, these proteins are thought to act as a mechanism to detoxify ester-containing xenobiotics. As a consequence, they are expressed in tissues that might be exposed to such agents (lung and gut epithelia, liver, kidney, etc.). CEs demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(64 citation statements)
references
References 23 publications
(32 reference statements)
2
59
0
Order By: Relevance
“…concentrations of SN-38 and SN-38G (Hatfield et al, 2016). This provides evidence of the importance of UDPGA and NADPH as enzyme co-factors in the metabolism of CPT-11.…”
Section: Metabolism Of Cpt-11 In Human Liver Microsomes With Differmentioning
confidence: 63%
See 1 more Smart Citation
“…concentrations of SN-38 and SN-38G (Hatfield et al, 2016). This provides evidence of the importance of UDPGA and NADPH as enzyme co-factors in the metabolism of CPT-11.…”
Section: Metabolism Of Cpt-11 In Human Liver Microsomes With Differmentioning
confidence: 63%
“…Some studies have reported little variability in expression of CES1 in human liver microsomes compared with human liver (Hsieh, Lin, Chen, Huang, & Roffler, ). However, CES1 possesses lower catalytic activity for CPT‐11 hydrolysis to SN‐38 than CES2, resulting in lower concentrations of SN‐38 and SN‐38G (Hatfield et al, ). This provides evidence of the importance of UDPGA and NADPH as enzyme co‐factors in the metabolism of CPT‐11.…”
Section: Resultsmentioning
confidence: 99%
“…Organophosphates are detoxified by the action of carboxylesterase 15 . Carboxylesterases (β-esterase or non-specific esterases) are group of hydrolytic enzymes important in the metabolism and subsequent detoxification of many xenobiotic and endogenous compounds, including Ops 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Research on mammalian carboxylesterases has primarily focused on their role in xenobiotic metabolism [4]. They metabolize and increase the clearance of drugs such as methylphenidate [5] and pesticides including pyrethroids [6].…”
Section: Introductionmentioning
confidence: 99%